Submerged membrane photocatalytic reactor using polyvinylidene fluoride-polyvinylpyrrolidonetitanium dioxide for oily wastewater treatment - Ong, Chi Siang (2015)
The objective of this study is to develop submerged polyvinylidene fluoride (PVDF) based hollow fiber ultrafiltration (UF) membranes with improved separation properties for oily wastewater treatment in which the membranes can also act as photocatalysis medium. The prepared membranes were characterized with respect to their morphological structure, surface roughness, hydrophilicity and separation performances. In the first stage of this study, PVDF based hollow fiber membranes incorporated with different titanium dioxide (TiO2) loading (0-4 wt%) were fabricated. The results indicated that when 2 wt.% TiO2 was incorporated into PVDF membranes, the permeate flux and oil rejection of 70.48 L/m2.h and 99.7 %, respectively, could be obtained when tested using 250 ppm synthesized oily solution under vacuum condition. With increasing feed oil concentration from 250 to 1000 ppm, the permeate flux was declined but oil rejection was improved. In the second stage of study, PVDF membrane consists of 2 wt.% TiO2 was further investigated by incorporating different molecular weight (Mw) of polyvinylpyrrolidone (PVP) (10, 24, 40, 360 kDa) and the membrane filtration performance and water flux recovery were performed. The obtained results revealed that PVDF-TiO2 composite membrane prepared from PVP 40kDa was the best performing membrane owing to its promising water flux (72.2 L/m2.h) coupled with good rejection of oil (94 %). It is also found that with increasing PVP Mw, membrane tended to exhibit higher PVP and protein rejection, greater mechanical strength, smaller porosity and smoother surface layer. Regarding to the effect of pH, the permeate flux of the PVDFPVP40k membrane was reported to increase with increasing pH from 4 to 7, however, showed a decrease when pH was further increased to 10. A simple backflushing process could retrieve approximately 60 % of the membrane original flux without affecting the oil separation efficiency. The membranes were further studied by integrating with photocatalysis process. The investigation of various operating parameters such as TiO2 catalyst loading, membrane module packing density, feed oil concentration and air bubble flow rates (ABFR) on the permeate flux, oil rejection and total organic carbon (TOC) degradation (in the bulk feed solution) were conducted. The average flux was reported to be around 73.04 L/m2.h using PVDF membrane incorporated with 2 wt.% TiO2 at 250 ppm oil concentration with module packing density of 35.3 % and ABFR of 5 L/min. A remarkable TOC degradation and oil rejection as high as 80 % and > 90 %, respectively, could be reached under these operating conditions. In the final stage, an attempt was made to evaluate the effects of UV irradiation period on the membrane (2 wt.% TiO2) by exposing the membrane to UV light for up to 250 h. It was observed that permeate flux was increased and some cracks and fractures were formed on the membrane outer surface when it was exposed to 120 h UV light. Furthermore, the mechanical strength and thermal stability of irradiated membrane were also reported to decrease with increasing UV exposure time, suggesting a membrane made of excellent UV resistant polymer is highly required. The overall findings shown in this study provide useful information for the research of separation and degradation of oily wastewater and facilitate the development of hybrid submerged membrane photocatalytic reactor (SMPR)